Kepemimpinan Perempuan dalam Pesantren - Ahmad Yusuf Prasetiawan; Safitri Lis (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2019)
This paper was made with the aim to find out how women's leadership in Islamic boarding schools organizations, and acceptance of them. In general, the founding of a boarding school has never been found where the caregivers are primarily women, even though they have more scientific capacity. Some Islamic boarding schools are cared for by women as limited successors. Islamic boarding schools are Islamic education institutions, the social construction of women in Islamic boarding schools is inseparable from the Islamic view of women. Not a few Islamic boarding schools whose daughter's activities are more advanced. Not a few managers of Islamic boarding schools where female carers' abilities are better. This paper is a descriptive analytical study of the phenomenon of women's leadership in Islamic boarding schools, with qualitative field studies. The results showed that women's leadership in Islamic boarding schools had the same chance of success, there were no substantive obstacles, because technically it could be covered by the Board of Directors, but female leaders in Islamic boarding schools were perceived as temporary and merely successors. The characteristics of women's leadership have a lot of relevance to the style of pesantren traditionalism, which is authoritative charismatic. The benefits of female leadership in Islamic boarding schools are to counter the Islamic stereotypical ideas about women.